On sandwich theorems for some subclasses defined by generalized hypergeometric functions - ALI, Ekram Elsayed; EL-ASHWAH, Rabha Mohamed; AOUF, Mohamed Kamal (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In this paper we derive some subordination and superordination results for certain normalized analytic functions in the open unit disc, which are acted upon by a class of generalized hypergeometric function Hq,s(α1). Mathematics Subject Classification (2010): 30C45, 30C80.